Efektivitas Penggunaan Media Sosial Dalam Transparansi Perpajakan Sebagai Upaya Peningkatan Kepercayaan Publik (Studi Kasus Wajib Pajak KPP Pratama Cibitung) - Okvi Diani Salsabila; Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The use of social media today has an extraordinary trend. The influence of globalization makes the phenomenon of social media an effective means of delivering information. A study reports that the number of social media users continues to increase from year to year. This makes encourages tax offices to campaign for tax policies through social media. In addition, social media as a medium for delivering information can also be an effective platform for implementing aspects of good governance such as transparency. Information can be conveyed openly through social media so that it can attract public trust. In this study the author intends to find out the effectiveness of the use of social media in the implementation of public transparency, especially taxation related to public trust. This research focuses on the Primary Tax Office of Cibitung. The results of the study stated that the social media accounts of the Primary Tax Office of Cibitung were not effective enough in their use for tax campaigns. Several taxpayer informants interviewed by the author stated that there are still some obstacles in the Primary Tax Office of Cibitung